Dream Big: Effects of Capitals, Socioeconomic Status, Negative Culture, and Educational Aspirations Among the Senior High School Student Athletes - Lee, Chia-Wen; Yeh, Ming-Chia; Hung, Huang-Chia (Frontiers in Psychology, 2021)
To understand the impact of social, financial, and cultural capitals, and negative culture, and socioeconomic status of families on educational aspiration in the senior high school student athletes, it will be beneficial to promote their career developments. The purpose of this study is to explore the influence of ethnicity, year of sport experiences family income, the educational expectations of significant others, and the three aforementioned types of capital on educational aspiration among the senior high school student athletes. The study with sample of 262 U-18 male baseball student athletes and 20.20% of them had attained the qualifications to play on the national team was conducted. The results showed that monthly family income positively affected social capital and positively indirectly affected educational aspirations through social capital whereas monthly family income negatively affected negative culture and positively affected educational aspirations through negative culture. Moreover, social capital positively affected educational aspirations compared with negative culture negatively affected educational aspirations. The results serve as a reference for the formulation of educational policy as it relates to student athletes.